2017
DOI: 10.3390/molecules22050705
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein and Cancer Chemoprevention: The Link is Hot

Abstract: Cancer comprises a collection of related diseases characterized by the existence of altered cellular pathways resulting in an abnormal tendency for uncontrolled growth. A broad spectrum, coordinated, and personalized approach focused on targeting diverse oncogenic pathways with low toxicity and economic natural compounds can provide a real benefit as a chemopreventive and/or treatment of this complex disease. Oleuropein, a bioactive phenolic compound mainly present in olive oil and other natural sources, has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 73 publications
0
32
0
Order By: Relevance
“…To investigate the antioxidant effect observed after oleuropein administration, we measured the circulating levels of HT, which is a result of oleuropein biotransformation in the human body and is characterized by free radical scavenging . Thus, we performed in vitro study using platelets as a cellular source of Nox2‐derived ROS and demonstrated that HT‐treated platelets stimulated with collagen displayed impaired Nox2‐derived oxidative stress as documented by lowered p47 phox phosphorylation and isoprostane production.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the antioxidant effect observed after oleuropein administration, we measured the circulating levels of HT, which is a result of oleuropein biotransformation in the human body and is characterized by free radical scavenging . Thus, we performed in vitro study using platelets as a cellular source of Nox2‐derived ROS and demonstrated that HT‐treated platelets stimulated with collagen displayed impaired Nox2‐derived oxidative stress as documented by lowered p47 phox phosphorylation and isoprostane production.…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer activities of OOPs, particularly of phenolic alcohol HTyr and secoiridoid polyphenols Ole and Oc, were largely investigated in the past decades and subsequently reviewed (23,26,33,(55)(56)(57)(58) (Fig. 2).…”
Section: Anticancer Effects Of Olive Oil Polyphenolsmentioning
confidence: 99%
“…Olive oil (OO) phenolic compounds exert a possible chemoprotective and anticancer activities in different types of cancer cells (23,(31)(32)(33): breast cancer (BC) (34,35), colon (36), prostate (37), melanoma (38), promyelocytic leukemia (39) and other cancer cells. Within the few last years, a growing interest in the collective effects of chemotherapeutics in combina-tion with OOPs was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, it is interesting to observe a correlation between phytochemicals profile identified by HPLC/MS and the selectivity degree of the extracts. FL1 and FL5 were selective towards the two cancer cell lines, and this may be due to the high content of oleuropein and ligstrosidic acid detected in the two extracts; oleuropein is a characteristic phenol largely distributed in Oleaceae family, and involved in a number of exhaustively documented biological activities [62]. Oleuropein exhibited cytotoxic activity against six tumoral cell lines, MCF-7, HepG2, Caco-2, A549, MDA, and DU145 [63].…”
Section: Plos Onementioning
confidence: 99%